Identification of Underwater Mountains Using Multibeam Echosounder Data (Case Research of the Waters of Southern Java) - Jhohan Irmanzah; Dwi Arini; Ilham Armi; Dwi Marsiska; Defwaldi Defwaldi (Green Publisher Indonesia, 2025)
Submarine mountains (seamounts) are important geological features formed by volcanic activity on the seafloor. Their identification and mapping play a crucial role in understanding geological dynamics, conserving marine ecosystems, and supporting sustainable resource management. This research focuses on the identification of seamounts in the southern waters of Java, Indonesia, using Multibeam Echosounder (MBES) data. The MBES data were processed and analyzed with Teledyne Marine PDS hydrographic software to produce bathymetric maps and Digital Elevation Models (DEM). The DEM enabled a detailed visualization of the seafloor morphology, including height, slope gradient, and peak shape of the identified seamounts. The analysis also assessed data accuracy in accordance with International Hydrographic Organization (IHO) standards, confirming that the mapping results met IHO accuracy requirements. This methodological approach demonstrates the capability of MBES and PDS processing to generate reliable topographic information for underwater geological studies. The findings highlight the existence of distinct seamounts in the southern Java waters, providing valuable insights into the region’s marine geology. Furthermore, the results contribute to more accurate hydrographic mapping, ecosystem conservation strategies, and sustainable resource exploration in Indonesia. Overall, this study emphasizes the significance of advanced hydrographic technologies in exploring poorly understood seafloor environments and provides a solid reference for future research on submarine topography.